Аналитическая модель оценки капитальных затрат на построение городской оптической сети доступа следующего поколения - Крикун, В. С.; Ощепков, М. Ю.; Бриндзий, А. В. (Проблеми телекомунікацій, 2012)
The paper proposed an analytical model to estimate the capital cost of deployment next generation optical access (NGOA) network for the urban area. This model is used for solution the problems: of optical access technology selection; the optimal topology and network access scenario determination; the active and the passive network components on the site, backbone, distribution and subscriber areas definitions. One of the main objectives of the analytical model is to perform a techno-economic evaluating of different proposed solution for NGOA networks. This evaluation comprises a cost assessment of infrastructure and equipment which are dependent on the network dimensioning and the area where they will be used. Proposed in paper an analytical model is different from the earlier known more fully into account the factors and components which form the optical access network. In this paper the problem of synthesizing the structure of next generation urban optical access network is formulated as an optimization, and it is based on the proposed analytical model. Demonstrated an example of using this analytical model for structural and parametric synthesis of urban next generation optical access network for the one of the Kharkiv regions.
Keywords: сеть доступа; аналитическая модель; сценарий развития; оптическая сеть; участок сети